Grain refinement in medium chromium ferritic stainless steel welds via aluminum powder addition - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Trans Tech Publications, 2012)
Grain refinement in medium chromium ferritic stainless steel weld was attempted via elemental (aluminum) powder pre-placement technique prior to melting under a TIG torch. A Box- Behnken experimental design was adopted with current, travel speed and the amount of aluminum powder added as the process factors for producing weld pool. The resolidified weld tracks were characterized using microscopy, microhardness and mechanical testing. The degree of grain refinement achieved was evaluated using a scaling index known as Grain Refinement Index (GRI). The findings showed that the GRI is influenced by the concentration of the aluminum powder introduced into the melt pool. Furthermore, high GRI does not necessarily translate to better mechanical properties relative to the conventional weld. This suggests that the grain size effect might not be the only factor influencing the property of weld metal. However, weld track treated with 0.08mg/mm2 of aluminum powder exhibited about 20% improvement in properties relative to the conventional weld made under the same energy conditions.